The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/112067210901900533
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Cocaine-Induced Maculopathy

Abstract: Ocular complications from topical cocaine abuse are rare. Impaired color vision, as in our patient, has been reported in cocaine-withdrawn patients. To our knowledge, this is the first described case of a bilateral and symmetric maculopathy associated with long-term intranasal cocaine use. To avoid a delay of treatment, ophthalmologists should be aware that a maculopathy with small defects in color vision may be related to adulterants added to cocaine when it is used intranasally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…[26] A class of designer drugs, the alkyl nitrites, including isopropyl nitrite and isobutyl nitrite, has been implicated in “poppers maculopathy.”[27,28,29] The offending agent is inhaled. Symptoms include decreased central visual acuity, central scotoma, phosphenes, and metamorphopsia.…”
Section: Retinamentioning
confidence: 99%
“…[26] A class of designer drugs, the alkyl nitrites, including isopropyl nitrite and isobutyl nitrite, has been implicated in “poppers maculopathy.”[27,28,29] The offending agent is inhaled. Symptoms include decreased central visual acuity, central scotoma, phosphenes, and metamorphopsia.…”
Section: Retinamentioning
confidence: 99%
“…81,143 For example, heroin is sometimes known to be cut with quinine, 82 cocaine has been reported to be cut with sodium bicarbonate, sugar, local anaesthetics, amphetamines, caffeine, or heroin. 66 Fourth, many news drugs are not detected by the regular screenings, which may lead to underreporting of drug-related ocular effects. 170 Lastly, the review of the evidence in this scoping review was mainly conducted by only one of the authors (VP), with partial validation by the other (BT).…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine is commonly reported to induce blue-yellow colour vision impairments. [64][65][66][67] Studies using OCT have commonly reported the thinning of superior, inferior and nasal retinal nerve fibre layers, 68 or a thinning of the superior retinal nerve fibre layer, which may mimic glaucoma. 69 Other occasional reports include a case of vascular headache secondary to consumption of cocaine that led to blurry vision, a case of transient monocular blindness following intranasal consumption and a case of chorioretinal ischaemia associated with a profound loss of vision.…”
Section: Cocainementioning
confidence: 99%
“…Substanzen. Der kaukasische [28], normotone [27,29] Patient war Nichtraucher [30] und betrieb keinen Missbrauch psychotroper Substanzen [31]. vermehrten psychologischen Problemen [34,35] in Zusammenhang gebracht.…”
unclassified